Protection of Foreign Famous Brands Based on the First to File Principle in MONSTER and 4MONSTER Disputes - Shelly Khalimatus Shafira; Andry Setiawan (Universitas Negeri Semarang, 2026)
This study aims to analyze the application of the first to file principle in providing legal protection to trademark rights holders in Indonesia, especially in trademark disputes involving well known brands. The background of this research is based on the fact that there is still a frequent conflict between legal certainty for the first registrant and substantive justice for those who have a reputation and use of the trademark first. This research is urgent due to ongoing issues concerning practice of trademark registration carried out in bad faith, which has the potential to cause unfair business competition and harm the owner of the brand in good faith. This research uses a normative juridical method with a legislative approach and a case approach, which focuses on Decision Number 12/Pdt.Sus-HKI/Memerk/2024/PN Niaga Central Jakarta related to the MONSTER and 4MONSTER trademark disputes. The originality of this research lies in its analysis of the application of the first to file principle in the latest commercial court decisions with an emphasis on the consideration of bad faith and the protection of well-known brands. The findings of the study show that although the Indonesian trademark legal system adheres to the principle of first to file which is constitutive, legal protection is not provided absolutely if the trademark registration is conducted in bad faith. This article concludes that the ruling strengthens substantive justice and provides important guidelines in balancing legal certainty and fairness in trademark law enforcement in Indonesia.